Prevalence and associated factors of female genital mutilation among Somali refugees in eastern Ethiopia: a cross-sectional study - Deressa Wakgari; Mitike Getnet (BMC, 2009)
Abstract Background Eastern Ethiopia hosts a substantial number of refugees originated from Somalia. Female genital mutilation (FGM) is a common practice in the area, despite the campaigns to eliminate it. Methods A cross-sectional study was conducted among 492 respondents sampled from three refugee camps in Somali Regional State, Eastern Ethiopia, to determine the prevalence and associated factors of FGM. Data were collected using pre-tested structured questionnaires. Results Although the intention of the parents to circumcise their daughters was high (84%), 42.4% of 288 ≤12 girls were reported being undergone FGM. The prevalence increased with age, and about 52% and 95% were circumcised at the age of 7-8 and 11-12 years, respectively. Almost all operations were performed by traditional circumcisers (81%) and birth attendants (18%). Clitoral cutting (64%) and narrowing of the vaginal opening through stitching (36%) were the two common forms of FGM reported by the respondents. Participation of the parents in anti-FGM interventions is statistically associated with lower practice and intention of the procedures. Conclusion FGM is widely practised among the Somali refugee community in Eastern Ethiopia, and there was a considerable support for the continuation of the practice particularly among women. The findings indicate a reported shift of FGM from its severe form to milder clitoral cutting. More men than women positively viewed anti-FGM interventions, and fewer men than women had the intention to let their daughters undergo FGM, indicating the need to involve men in anti-FGM activities.